A matter of style? Driver attributional 'style' in accounting for the driving of others as protective or as predisposing drivers towards retaliatory aggressive driving. (April 2015) - Lennon, Alexia J.; Watson, Barry C.
Highlights: Attributions about another drivers' behaviour may reflect attributional styles. Higher anger was associated with attributions that others were unskilled or dangerous. More aggressive responses were associated with attributions of unskilled or dangerous. Style giving others 'benefit of the doubt' appear protective (less angry, aggressive). Drivers respond with greater aggression when others perceived as intentionally aggressive. Abstract: Driver cognitions about aggressive driving of others are potentially important to the development of evidence-based interventions. Previous research has suggested that perceptions that other drivers are intentionally aggressive may influence recipient driver anger and subsequent aggressive responses. Accordingly, recent research on aggressive driving has attempted to distinguish between intentional and unintentional motives in relation to problem driving behaviours. This study assessed driver cognitive responses to common potentially provocative hypothetical driving scenarios to explore the role of attributions in driver aggression. A convenience sample of 315 general drivers 16–64 yrs ( M = 34) completed a survey measuring trait aggression (Aggression Questionnaire AQ), driving anger (Driving Anger Scale, DAS), and a proxy measure of aggressive driving behaviour (Australian Propensity for Angry Driving AusPADS). Purpose designed items asked for drivers' 'most likely' thought in response to AusPADS scenarios. Response options were equivalent to causal attributions about the other driver. Patterns in endorsements of attribution responses to the scenarios suggested that drivers tended to adopt a particular perception of the driving of others regardless of the depicted circumstances: a driving attributional style. No gender or age differences were found for attributional style. Significant differences were detected between attributional styles for driving anger and endorsement of aggressive responses to driving situations. Drivers who attributed the on-road event to the other being an incompetent or dangerous driver had significantly higher driving anger scores and endorsed significantly more aggressive driving responses than those drivers who attributed other driver's behaviour to mistakes. In contrast, drivers who gave others the 'benefit of the doubt' endorsed significantly less aggressive driving responses than either of these other two groups, suggesting that this style is protective.